2019
DOI: 10.13057/ijap.v9i02.31700
|View full text |Cite
|
Sign up to set email alerts
|

Efek Penggunaan Cairan Ionik sebagai Aditif terhadap Konduktivitas Ionik Elektrolit Baterai Ion Litium

Abstract: Lithium ion battery technology is an alternative energy supply for portable equipment, electronics devices and high power applications such as electric vehicle and power storage for renewable energy. Electrolyte of lithium ion battery plays an important role in determining battery performance. It consists of lithium salt, commonly use lithium hexafluorophosphate (LiPF6), dissolved in organic carbonate solvent and additives. However, LiPF6 is thermally unstable and influence battery performance significantly. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Garam ini merupakan elektrolit kuat yang mampu terionisasi dan menghantarkan listrik sehingga kulit pisang bisa bertindak sebagai elektrolit pada baterai (Muhlisin et al, 2015). Keberadaan garam pada elektrolit baterai sangat penting karena dapat meningkatkan konduktivitas ionik sehingga menghasilkan transport ion yang lebih baik (Septiana, Kartini, Honggowiranto, Sudaryanto, & Hidayat, 2019). Garam kalium klorida akan terionisasi menjadi ion kalium dan klorida, sehingga bisa menghantarkan listrik.…”
Section: Kulit Pisangunclassified
“…Garam ini merupakan elektrolit kuat yang mampu terionisasi dan menghantarkan listrik sehingga kulit pisang bisa bertindak sebagai elektrolit pada baterai (Muhlisin et al, 2015). Keberadaan garam pada elektrolit baterai sangat penting karena dapat meningkatkan konduktivitas ionik sehingga menghasilkan transport ion yang lebih baik (Septiana, Kartini, Honggowiranto, Sudaryanto, & Hidayat, 2019). Garam kalium klorida akan terionisasi menjadi ion kalium dan klorida, sehingga bisa menghantarkan listrik.…”
Section: Kulit Pisangunclassified
“…The organic solvent propylene carbonate (PC) has an advantage over other organic carbonate solvents because of its low price and good performance at low temperatures. 3 However, the use of PC in lithium ion batteries has problems due to the cointercalation of solvent molecules with 𝐿𝑖 + ions on graphite and causing flaking. Organic solvents such as ethylene carbonate (EC) can form a solid electrolyte interface layer that is more stable than other organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Related to this problem, using other lithium salts to replace LiPF6 has become very important, and LiTFSI is the most promising candidate as a substitute for LiPF6. LiTFSI can be used as an electrolyte in lithium-ion batteries due to its high conductivity, insensitivity to moisture, high thermal stability, and electrochemical stability compared to LiPF6 (Septiana, Kartini, Honggowiranto, Sudaryanto, & Hidayat, 2019). The ionic conductivity and lithium transfer number ideal of LiTFSI are above 10 -1 mS/cm (Goodenough & Kim, 2010); the ideal LTN is equal to 1 (Zhang et al, 2017); the cyclic voltammetry of electrolytes with imide additives display higher current densities between 4.5 and 5.3 V vs Li/Li + than the bare electrolyte (Sharova et al, 2018); CD analysis of LiTFI showed that charge-discharge occurs.…”
Section: Introductionmentioning
confidence: 99%